The preparation and characterization of uniform nanoporous structure on glass. Issue 7 (8th July 2020) - Wang, Lei; Li, Likai; Liu, Youbo; Wang, Shuxian; Cai, Hui; Jin, Hao; Tang, Qingwen; Sun, Wei; Yang, Deren
Abstract : A novel fabrication method of uniform porous structures on the glass surface is proposed. The hydrofluoric acid fog formed by air-jet atomization etches the glass surface to fabricate nanoporous structure (NPS) on glass surface. This NPS shows the enhanced average light transmittance of approximately 92.9% and the superhydrophilic property with a contact angle less than 1° which presents an excellent anti-fog property. Passivated by fluorosilane, the NPS shows nearly the superhydrophobic property with a contact angle of 141.2°. This fabrication method has shown promising application prospects due to its simplicity, low cost and efficiency, which can be easily applied to large-scale industrial production.